Women's autonomy in refusing risky sex in sub-Saharan Africa: Evidence from 30 countries. - Eugene Budu; Bright Opoku Ahinkorah; Joshua Okyere; Abdul-Aziz Seidu; Richard Gyan Aboagye; Sanni Yaya (Public Library of Science (PLoS), 2023)
Understanding the factors associated with women's autonomy to refuse risky sex is imperative to inform the development of policies and interventions to reduce the risk of unintended pregnancies, sexually transmitted infections, unsafe abortion, and maternal mortality. This study sought to examine the prevalence and factors associated with women's autonomy to refuse risky sex in sub-Saharan Africa (SSA). Data for the study were extracted from the most recent Demographic and Health Surveys (DHS) of thirty countries in SSA conducted from 2010 to 2020. We included a weighted sample of 260,025 women who were married or cohabiting in the final analysis. Percentages were used to present the results of the prevalence of women's ability to refuse risky sex. We used a multilevel logistic regression analysis to examine the factors associated with women's ability to refuse risky sex. Stata software version 16.0 was used for the analysis. We found that 61.69% (95% confidence interval [CI]: 56.22-67.15) of the women were autonomous to refuse sex if their partners have other women, and this was highest in Namibia (91.44% [95% CI: 90.77-92.18]) and lowest in Mali (22.25% [95% CI: 21.24-23.26]). The odds of autonomy in refusing risky sex was higher among women with higher education (adjusted odds ratio [aOR] = 1.88; 95% CI = 1.78-1.46) compared to those with no formal education. Employment status was also a significant predictor, with working women having higher odds of sex refusal compared to non-working women (aOR = 1.16; 95% CI = 1.13-1.18). Advocacy to improve women's autonomy to refuse risky sex must leverage the mass media as it emerged as a significant factor. Policies and intervention to enhance women's autonomy must also target high-risk sub-populations which constitutes adolescent girls, those with no formal education, and those without employment.